2010
DOI: 10.1200/jco.2010.28.5031
|View full text |Cite
|
Sign up to set email alerts
|

Single-Agent Arsenic Trioxide in the Treatment of Newly Diagnosed Acute Promyelocytic Leukemia: Long-Term Follow-Up Data

Abstract: PURPOSE We previously reported our results with a single-agent arsenic trioxide (ATO) -based regimen in newly diagnosed cases of acute promyelocytic leukemia (APL). The concern remained about the long-term outcome of this well-tolerated regimen. We report our long-term follow-up data on the same cohort. PATIENTS AND METHODS From January 1998 to December 2004, 72 patients with PML/RARalpha+ APL were enrolled. All patients were treated with a single-agent ATO regimen. Results Overall 62 (86.1%) achieved a hemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(166 citation statements)
references
References 15 publications
2
163
0
1
Order By: Relevance
“…47 Future studies should further delineate the arsenic/PML interactions, as they clearly underlie therapeutic response and cure of APL upon arsenic therapy (see below). 84 PML NBs were once envisioned as simple depots where cellular or viral proteins were sequestered or stored. 85,86 Yet, a more complex view has recently emerged wherein sumoylated partners may be modified by other NB-associated enzymes, particularly enzymes controlling various post-translational modifications.…”
Section: Biochemical Consequences Of Partner Recruitmentmentioning
confidence: 99%
“…47 Future studies should further delineate the arsenic/PML interactions, as they clearly underlie therapeutic response and cure of APL upon arsenic therapy (see below). 84 PML NBs were once envisioned as simple depots where cellular or viral proteins were sequestered or stored. 85,86 Yet, a more complex view has recently emerged wherein sumoylated partners may be modified by other NB-associated enzymes, particularly enzymes controlling various post-translational modifications.…”
Section: Biochemical Consequences Of Partner Recruitmentmentioning
confidence: 99%
“…This model has been progressively questioned by several subsequent findings. In particular, arsenic treatment, which does not directly activate PML/RARA-dependent transcription and fails to induce significant ex vivo differentiation, can cure up to 70% of patients when used as single agent (51)(52)(53)(54). Similarly, although the RA-arsenic combination antagonizes differentiation ( 51 ), it is actually synergistic with regard to APL cell clearance, culminating in disease eradication in mice as well as in humans ( 21 , 55 ).…”
Section: Adult T-cell Leukemiamentioning
confidence: 99%
“…Clearly, strategies for further improvement of therapeutic ratio in the management of cervical cancer with radiation-based treatment are needed. As 2 O 3 is an agent successfully employed in the treatment of APL with limited side effects [11][12][13]. It was found to induce growth inhibition and apoptosis in solid tumors [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…It has been used to treat a variety of conditions including cancer [9,10]. As 2 O 3 has been proven efficacious in the treatment of acute promyelocytic leukemia (APL) with limited adverse effects [11][12][13]. It has been demonstrated that As 2 O 3 can affect cellular signal transduction pathways and cross-talks of signal molecules which include downregulation of Bcl-2 protein, activation of caspase, direct mitochondrial damage, promotion of tubulin polymerization [14], and some of the abovementioned mechanisms are involved in radiosensitization.…”
Section: Introductionmentioning
confidence: 99%